2014
DOI: 10.1111/sltb.12110
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric and Self‐Injury Profiles of Adolescent Suicide Attempters versus Adolescents Engaged in Nonsuicidal Self‐Injury

Abstract: To better delineate the unique correlates of self-injurious behaviors (SIB), psychiatric profiles of mutually exclusive groups of adolescents who made a suicide attempt (SA) versus those engaged in nonsuicidal self-injury (NSSI) were examined. Contrary to hypotheses, the NSSI group endorsed earlier onsets of SIB and suicidal ideation (SI), as well as higher rates of depression and anxiety compared with their SA counterparts. Future work is warranted to understand the role of SI, including duration of SI and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…The KSADS‐PL was administered only to NSSI and SA participants and not their parents due to logistical constraints of assessing an inpatient population (e.g., short lengths of stay, somewhat limited access to family members). Our previously published examination of psychopathology in this sample confirms a high correlation between NSSI and SA participant KSADS‐PL diagnoses and parent completed reports about psychopathology (Kim et al., ).…”
Section: Methodssupporting
confidence: 85%
See 3 more Smart Citations
“…The KSADS‐PL was administered only to NSSI and SA participants and not their parents due to logistical constraints of assessing an inpatient population (e.g., short lengths of stay, somewhat limited access to family members). Our previously published examination of psychopathology in this sample confirms a high correlation between NSSI and SA participant KSADS‐PL diagnoses and parent completed reports about psychopathology (Kim et al., ).…”
Section: Methodssupporting
confidence: 85%
“…Another interpretation is that NSSI provides a coping strategy to avert an SA (Nock & Prinstein, ). In our prior study of psychopathology among this group of adolescents engaged in either NSSI‐only or SA‐only, we found that NSSI participants were significantly more likely to report engaging in self‐harm to cope with their current emotional state than SA participants, whereas SA participants were more likely to endorse escaping from someone or something (Kim et al., ). This aligns with Nock and Prinstein's four‐function model of NSSI, suggesting that NSSI is an automatically/self‐reinforcing process (rather than being reinforced by others) helping the individual cope with negative emotions (Klonsky & Olino, ; Nock & Prinstein, ).…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Despite the clear rationale for research on self-harm in autism, studies of self-harm often explicitly exclude autistic participants (see Kim et al 2015 ; Dickstein et al 2015 ). One possible reason for this exclusion is an a priori definition of self-harm that categorises the typically repetitive self-injurious behaviours exhibited by autistic people as qualitatively different to self-harm shown by neurotypical individuals.…”
mentioning
confidence: 99%